MENANAMKAN KONSEP PEMBELAJARAN BERBASIS STEAM (SCIENCE, TECHOLOGY, ENGINEERING, ART, AND MATHEMATHICS) PADA GURU-GURU SEKOLAH DASAR DI PACITAN - Yuyun Estriyanto (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2020)
ABSTRACT This article is a report of a community partnership program to introduce STEAM-based learning concepts (science, technology, engineering, art, and mathematics) for elementary school teachers in Pacitan Regency. STEAM-based learning is seen to be compatible with elementary thematic learning because they are not rigidly restricted by subjects, but an integration of various subjects that are packaged into a topic that could be discussed in terms of scientific, technological, engineering, artistic, and mathematical. The evaluation of the program is carried out using a questionnaire. It is found that after attending the training, the participants have a high enthusiasm for STEAM, a good understanding of the STEAM-based learning concepts, and able to see the compatibility with thematic learning in elementary schools. However, the participants still need further assistance to realize the concepts into real learning.